Pedagogia da imagem: a leitura iconográfica do mundo pela infância - Veronesi, Valquiria Bertuzzi (2022)
This research has as its object the contributions of images reading to the learning of 5-years-old children, covering the cognitive, affective and psychomotor domains, according to Benjamin Bloom’s taxonomy. It investigates the experience of images reading in public schools in a metropolitan region of São Paulo. Considering that images are available in contemporary society and influence children in different ways, answers were sought to the following questions: How is the reading of images, in Early Childhood Education worked? Do practices enhance learning, or are they merely reproductive activities? What skills and competences are stimulated? With this, it is essential to rethink what relationships, dialogues and proposals are being offered to children’s curiosity, questions and discoveries. The reading of images from the perspective of meaningful reading of the world was discussed, since this practice brings important elements for children to communicate, express themselves, reflect and expand the possibilities of understanding themselves and the world around them. From a theoretical-methodological point of view, this thesis was based on some of Freire’s categories: curiosity, dialogue, reading the world and awareness. The concepts of Early Childhood Education, image, image reading were discussed, with contributions from Lev Semenovich Vygotsky, Régis Debray, José Eustáquio Romão and Ana Mae Barbosa. The investigation, of a quantitative-qualitative nature, began with the survey of opinion trends, based on the Likert Scale, with teachers and children, defining the experimental and control universes. In the in-depth research, semi-structured interviews were carried out with the children and the teachers and, finally, with the children, Paulo Freire’s foundations were used in his Culture Circles, reinvented and named Epistemological Circles, as a research methodology, according to with Romão. The investigation confirmed the hypothesis and demonstrated how children are able to build knowledge in the face of the regularity of emancipatory practices, such as images reading, reaching the point of exceeding the expectations of the educational objectives, provided for in Bloom’s taxonomy.